Modernity’s Influence on Islam: Analyzing Abul Hasan Ali Nadwi’s Revivalism in 20th Century India - Raza, Ahsan (El Tarikh : Journal of History, Culture and Islamic Civilization, 2024)
The twentieth century witnessed intense debates among Intellectuals of social sciences as they grappled with dichotomies such as East versus West, culture versus nature, religion versus atheism and orient versus occident. Within this discourse, heated debates emerged surrounding modern civilization and its global impact. The Western dominance, propelled by technological advancements, not only challenged the perceived superiority of Islam as a beacon of humanity but also necessitated a reorientation of its stance to meet contemporary demands. India was also fortunate to have Abul Hasan Ali Nadwi, commonly known as Ali Miyan, who was a prolific writer, reformer, and political thinker. Through his books, travelogues, lectures, articles, seminar and conference papers, as well as his efforts in Da’wah and his movement of Payame Insaniyat, he tirelessly sought to counter the ideologies propagated by the West. In this paper, I aim to shed light on the revivalist endeavors championed by Ali Miyan Nadwi, aimed at countering Western modernity. Additionally, I would like to analyze the debates surrounding cultural differences, religious manifestations, and philosophical undercurrents and how this process inadvertently contributed to a state of chaos within Muslim society.